Rhabdomyolysis and myoglobinuria following single induction dose of propofol in a dog. Issue 1 (23rd July 2022) - Cervone, Mario; Nectoux, Alexandra; Pouzot‐Nevoret, Celine
Abstract: Objective: To report a case of rhabdomyolysis and myoglobinuria following single induction dose of propofol in a dog. Case Summary: A 5‐year‐old intact male Shih‐Tzu dog was presented for pigmenturia occurring a few hours following anesthesia for comprehensive oral health assessment and treatment. After premedication with IV diazepam (0.5 mg/kg), anesthesia was induced with IV propofol (4 mg/kg) and maintained with isoflurane vaporized in oxygen. A few hours following recovery from anesthesia, the dog developed rhabdomyolysis and myoglobinuria associated with increased serum alanine aminotransferase and C‐reactive protein concentrations, as well as mild hypokalemia and euglycemic glycosuria. Approximately 48 hours after IV fluid therapy, the dog was clinically normal, and myoglobinuria progressively resolved. New or Unique Information Provided: This is the first case description of rhabdomyolysis and myoglobinuria following a single dose of injectable propofol.